2017
DOI: 10.5812/asjsm.13778
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Supportive Psychotherapy to Prevent Posttraumatic Stress Disorder: A Cross Sectional Study on the Iranian National Under-14 Girls’ Football Team After Nepal Earthquake in 2015

Abstract: Background: Earthquakes are devastating natural disasters. When an earthquake occurs during a significant event, such as Asian football confederation (AFC) under-14 girls' regional championship in Nepal (2015), all catastrophic casualties should be taken into account, including mental side effects on young sensitive groups. The present paper aimed to report risk-reduction activities for posttraumatic stress disorder (PTSD) in 18 young members of the Iranian football team.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…When it comes to other aspects of health in young female players such as psychological issues, our knowledge is still lacking (11). A recent study reported that male football players had significantly lower average depression and anxiety scores than female football players.…”
mentioning
confidence: 99%
“…When it comes to other aspects of health in young female players such as psychological issues, our knowledge is still lacking (11). A recent study reported that male football players had significantly lower average depression and anxiety scores than female football players.…”
mentioning
confidence: 99%